Biochemical profile of diabetic ketoacidosis in type 2 diabetes patients: an observational study - More, Hardik; Patil, Dilip; Singh, Chahat (International Journal of Advances in Medicine, 2024)
Background: The present study was conducted to assess the clinical profile of type 2 diabetes patients presenting with diabetic ketoacidosis and review their biochemical parameters at the time of presentation. Methods: The present study was an analytical, cross-sectional study conducted over the period of two years. All the type 2 diabetes patients with diabetic ketoacidosis admitted during the study period constituted the study population, after being subjected to prefixed selection criteria. All the participants were subjected to detailed clinical examination and biochemical analysis during hospitalization and parameters were monitored. Results: Out of the total 60 type 2 DM patients with DKA studied, 53.3% patients belonged to 51 to 60 years age group and 55% were males. One patient died and 59 survived (mortality rate-1.6%). Comparatively higher mean RBS, higher mean serum osmolality and lower pH were observed in the death case in comparison with those who survived. The patient who died had no statistically significant difference in serum sodium, potassium, calcium and magnesium but had lower serum HCO3- than alive patients on admission. Conclusions: DKA is a serious metabolic complication even in cases of type 2 diabetes and higher RBS, higher Sr Osmolality and lower pH at the time of presentation correlate directly with poorer outcomes.